SOCIAL DISCRIMINATION IN MIKE NEWELL’S PRINCE OF PERSIA (2010): A SOCIOLOGICAL APPROACH - FACHRUDIN, AR (2011)
The main aim of this study is to find how discrimination is reflected in Mike Newell’s Prince of Persia by correlating its structural elements and social historical background of Persia in ninth century. Indeed, literature and sociology are bounded each other due to the assumption that the appearance of literary work is in social emptiness. This study uses qualitative method in which the data are taken from both primary and secondary data source in form of words, sentence and phrases. Primary data source is Mike Newell’s Prince of Persia meanwhile secondary data sources are other sources related to the primary data. Data collecting method in this study is library research, and in analyzing the data the researcher employs descriptive analysis. The outcomes of this study are as follows: (1) Mike Newell’s Prince of Persia reflects social condition occurred in ninth century of Persia. (2) Mike Newell’s depicts social discrimination that creates crimes in Prince of Persia. (3) Prince of Persia is Mike Newell’ satire and criticism toward unbalance situation and condition that can be found in character’s characterization, narration and dialogue.